Caught in the Crossfire: Bangladesh’s Erosion of Human Rights in the Battle Against Terrorism and Religious Extremism - Gabbay, Shaul M. (Advances in Social Sciences Research Journal, 2023)
Egregious human rights violations are prevalent in Bangladesh, with torture and ill-treatment deeply ingrained within the country’s law enforcement agencies, intelligence organizations, paramilitary groups, and security forces. This paper explores the rampant use of torture as a powerful tool to suppress political opponents, silence dissenting voices, and control vulnerable communities, while instilling fear among ordinary citizens. Despite enacting legislation and ratifying international conventions against torture, Bangladesh continues to struggle with a culture of impunity and lack of implementation, hindering independent investigations and delayed prosecutions. The historical context reveals the roots of violence and torture in Bangladesh, including the tragic genocide in 1971. Political instability, polarization, and the rise of religious extremism have further exacerbated the issue. The international dimension highlights external pressures, particularly from the United States and its allies, urging Bangladesh to combat terrorism and religious extremism. As a critical player in regional counterterrorism efforts, Bangladesh faces the challenge of balancing strong measures with human rights protection. The paper emphasizes the need for comprehensive reforms, strengthened accountability, and independent investigations to address the deeply ingrained practice of torture. By upholding international obligations, fostering a culture of transparency, and respecting human rights, Bangladesh can pave the way for a more equitable and rights-respecting society. Only through concerted efforts can the legacy of violence and torture be transformed into a commitment to protect the dignity and rights of all its citizens, ensuring a brighter future for Bangladesh and its people